Factors Forming Transport-Communication Infrastructure of the Region: Russian Theory and Practice - BLAGININ, Viktor A.; KARKH, Dmitriy A.; KOLOTNINA, Elena V. (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017DO - 10.14505//jemt.v8.3(19).17, 2017)
The paper presents a theoretical study of forming and functioning of the objects in the transport-communication infrastructure of the region, with the focus on an automobile transport infrastructure. The factors forming the infrastructure are stated on the basis of the comprehension of economic processes in modern Russia. In this country the process of diminution and narrowing of space is a configuration for an efficient interaction of regions and only the transport infrastructure can ensure its advanced development. Viewed from this aspect, an attempt to systemize the factors forming a motor transport infrastructure enables the authorities to project the current situation in the sector and to improve their policy of influence, in order to enhance the efficiency of its operation. The authors also conduct a study of the impact of transport infrastructure on the environment, namely, determining the degree of air pollution. The leading approach to the study of this problem is based on an analysis of the formation of factors that contribute to the contamination of the territory. Proceeding from this aspect, the attempt to systematize the factors that form the transport infrastructure allows the authorities to design the current situation in this sector and improve their policy of influence in order to improve the efficiency of its operation. An assessment is made of effective ways to minimize environmental impacts, taking into account possible significant consequences for the natural, social, technogenic environment.